Delusions in the nonclinical population. - Freeman, D (2006)
Delusions have long been considered a hallmark of psychotic disorders such as schizophrenia. However, delusions may only be most visibly present in psychotic conditions and could also occur in nonclinical groups. The aim of this review is to establish whether delusions, as traditionally considered and assessed in psychiatric conditions, are also present in individuals without a psychiatric or neurologic condition. Clear evidence is found that the rate of delusional beliefs in the general population is higher than the rate of psychotic disorders and that delusions occur in individuals without psychosis. The frequency of delusional beliefs in nonclinical populations varies according to the content of the delusion studied and the characteristics of the sample population. Approximately 1% to 3% of the nonclinical population have delusions of a level of severity comparable to clinical cases of psychosis. A further 5% to 6% of the nonclinical population have a delusion but not of such severity. Although less severe, these beliefs are associated with a range of social and emotional difficulties. A further 10% to 15% of the nonclinical population have fairly regular delusional ideation. There is convincing evidence that delusional ideation, delusions, and clinically severe delusions are related experiences. Information about clinical delusions can therefore be obtained by studying delusional ideation in nonclinical populations.